The Character Values of Hard Work in the Novels of Leila S. Chudori - Renita Br Saragih; Sahid Teguh Widodo; Nugraheni Eko Wardani (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2019)
Literary works are a media that has an important role in building character. One of the literary works is novels. A novel contributes the thoughts and ideas of the author through the language that aims to provide benefits to the readers. This study aimed to describe the character values of hard work in the novels of Leila S. Chudori. This was a qualitative research using descriptive qualitative method and content analysis. The data in this research were from the novels of Leila S. Chudori. The research results showed that the character values of hard work of the character were found through the implied words, phrases, and sentences in the novels of Leila S. Chudori. The character values of hard work in the novels could be seen from how the character was persistent to achieve the goals, and able to find solutions for every problem. The characters of hard work reflected from the character could provide a value or message for the readers of the novels of Leila S. Chudori. The characters of hard work found in the two novels were: (1)unyielding attitude, (2) willingness to try, (3) living a life with positive thinking, and (4) character of struggling for life.